STRATEGI KEPALA SEKOLAH MELALUI SUPERVISI DALAM MENINGKATKAN KINERJA GURU - Adli, Adli (PASCASARJANA UNISNU, 2024)
This research is qualitative type with literature method. Information is collected through relevant references to be analyzed such as collecting information by recognizing discourse from various references such as books, papers or posts, journals, internet (websites) or other information in the form of data, magazines and so on related to the principal's strategy and supervision in improving teacher performance. Educational supervision plays an important role in providing guidance and support to teachers to develop effective learning strategies by utilizing information technology and evaluating the quality of learning. Principals have a strategic role by providing motivation, increasing teacher capacity, implementing supervision, and optimizing information technology in learning management. Good teacher performance is determined by the ability to master academic competencies, learning methods, work discipline, commitment to improving student achievement. Cooperation between principals, teachers and all school elements is very important to carry out supervision and education management to improve the quality of learning in a sustainable manner and in accordance with the times. The implementation of these strategies is expected to maximize the role of each element to improve the quality of learning processes and outcomes. This discussion is expected to provide an overview of the efforts made to improve the quality of learning through educational supervision, the role of the principal, and improving teacher performance.